Semi‐Transparent, Micrometer Resolution p‐NiO/n‐ZnO Heterojunction Diode Temperature Sensors with Ultrathin Metal Anode. Issue 6 (30th December 2021) - Lee, Junhee; Hong, Nari; Hong, Woongki; Kim, Duhee; Hwang, Yujin; Jang, Jaewon; Kang, Hongki
Abstract: Various temperature sensitive biological mechanisms have been utilized for new biomedical engineering tools such as neuromodulation, cancer cell hyperthermia or photothermal therapy. Optically transparent and high spatio‐temporal resolution temperature sensors are needed to precisely analyze the biological effects that occur in response to the temperature changes. In this work, semi‐transparent p‐NiO/n‐ZnO heterojunction diode‐based temperature sensors with 100 µm‐diameter ultrathin transparent Au/Ag metal anodes is introduced. The fabricated diode temperature sensors accurately measure temperature changes from 25 to 80 °C, which is of significant interest in many biomedical engineering applications. The sensors also exhibit adequate transparency over the entire visible light spectrum for biomedical imaging including fluorescent microscopy. Low‐power operation of the temperature sensor (<0.2 nW) is achieved to avoid a self‐heating effect. The micro‐scale spatial resolution of the transparent temperature sensors is especially useful for cellular resolution bio‐imaging, optical neural recording, and optical bio‐modulation where transparency and high‐resolution temperature sensing are necessary. Abstract : Optically transparent and high spatiotemporal resolution temperature sensors can enable precise analysis of various temperature sensitive biological mechanisms of cells with simultaneous bio imaging of the cells. In this work, semi‐transparent wide bandgap semiconductor heterojunction diode‐based temperature sensors with ultrathin transparent metal anodes is introduced. µm‐scale spatial and µs‐scale temporal resolutions are demonstrated with bio‐imaging demonstration using optical transparency.